2019
DOI: 10.1017/s0007114518003756
|View full text |Cite
|
Sign up to set email alerts
|

Increasing intake of dietary soluble nutrients affects digesta passage rate in the stomach of growing pigs

Abstract: The passage rate of solids and liquids through the gastrointestinal tract differs. Increased dietary nutrient solubility causes nutrients to shift from the solid to the liquid digesta fraction and potentially affect digesta passage kinetics. We quantified: (1) the effect of three levels of dietary nutrient solubility (8, 19 and 31 % of soluble protein and sucrose in the diet) at high feed intake level (S) and (2) the effect of lowv.high feed intake level (F), on digesta passage kinetics in forty male growing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…Solid fractions of digesta needed on average 4•9 h to pass the stomach and SI of young growing pigs, which is in line with previous research (10,11,39,40) . The effects of digesta passage behaviour on nutrient absorption kinetics were dominated by stomach MRT, as digesta MRT in the stomach was longer than that of the SI, which corresponds to previous research (11) . As expected (10,11) , we found that the passage rate for the liquid digesta fraction typically exceeded that of solids in the stomach, but not necessarily in the SI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Solid fractions of digesta needed on average 4•9 h to pass the stomach and SI of young growing pigs, which is in line with previous research (10,11,39,40) . The effects of digesta passage behaviour on nutrient absorption kinetics were dominated by stomach MRT, as digesta MRT in the stomach was longer than that of the SI, which corresponds to previous research (11) . As expected (10,11) , we found that the passage rate for the liquid digesta fraction typically exceeded that of solids in the stomach, but not necessarily in the SI.…”
Section: Discussionsupporting
confidence: 89%
“…The increase in fluidity after passage of the stomach is likely related to the lower DM content in the SI compared with the stomach (on average 13 %, data not shown). It is well known that solids are retained longer in the porcine stomach than liquids (10,11) , which is consistent with the difference in MRT between stomach liquids and solids, observed in our study. Usually, large particles (diameter > 1-2 mm) remain in the human stomach until the particle size is reduced sufficiently (16,18) .…”
Section: Rheological Characterisation Of Diets and Digestasupporting
confidence: 93%
“…Experimental conditions and the number of animals limit our capability to make conclusions on growth performance. Other factors such as feed intake and solubility of nutrients influence retention time of solids and liquids in the gastrointestinal tract, thereby changing the kinetics of nutrient flow (52) . Although soluble DF and diet viscosity might influence retention time (53) , how digesta viscosity regulates retention time, thereby altering nutrient digestibility cannot be discerned in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a dynamic stomach model was developed, mimicking a step-wise drop in pH ( Martens et al, 2020 ). In the small intestine, these methods focus on the solubilization of proteins and appearance of AA and small peptides, or glucose, during incubation with digestive enzymes, rather than harvesting the insoluble residue at the end of incubation ( Chen et al, 2019 ; Schop et al, 2019b ).…”
Section: In Vitro Methods To Characterize the Potential Feeding Valuementioning
confidence: 99%